Modyfication of the Rigid Polyurethane-Polyisocyanurate Foams - Bogusław Czupryński; Joanna Liszkowska; Joanna Paciorek-Sadowska (Journal of Chemistry)
The effect of polyethylene glycol 1500 on physicomechanical properties of rigid polyurethane-polyisocyanurate (PUR-PIR) foams has been studied. It was found that application of polyethylene glycol 1500 for synthesis of foams in amount from 0% to 20% w/w had an effect on reduction of brittleness and softening point, while the greater the increase in compressive strength the higher its content in foam composition was. Wastes from production of these foams were ground and subjected to glycolysis in diethylene glycol with the addition of ethanolamine and zinc stearate. Liquid brown products were obtained. Properties of the resulting products were defined in order to determine their suitability for synthesis of new foams. It was found that glycolysate 6 was the most suitable for reuse and its application in different amounts allowed us to prepare 4 new foams (nos. 25, 26, 27, and 28). Properties of foams prepared in this manner were determined and, on their basis, the suitability of glycolysates for production of rigid PUR-PIR foams was evaluated.